Can the Private Annuity Market Provide Secure Retirement Income? - Schrager, Allison (IMF Working Papers; Working Paper, 2004)
Annuity premiums are often assumed to be constant, although they can be expected to vary with the yield curve. Variations in premiums will become an important public policy issue as defined-contribution (DC) pension plans play an increasingly prominent role in providing retirement income. As DC plan holders retire, many will annuitize at least a part of their account balances. In the absence of current data on annuity prices, the paper relies on U.S. Treasury interest rate data to simulate the impact of interest rate variation on annuity premiums. For a spectrum of feasible interest rates, the variation in retirement income is not negligible.